A unique polymeric gel by thiol–alkyne click chemistry1. Issue 62 (8th July 2015) - Ganivada, Mutyala Naidu; Kumar, Pawan; Shunmugam, Raja
<x xml:space="preserve">Abstract</x> Poly(ethylene glycol) functionalized with tetra-acetylene (PTETACT) and pentaerythritol (3-mercaptopropionic acid) (PETM) are cross-linked by a thiol–yne reaction to create robust, tuneable networks.